Perencanaan Dan Perancangan Outfall Club di Desa Munggu Dengan Pendekatan Arsitektur Organik - I Made Bisma Dwipa Yadnya; I Wayan Wirya Sastrawan; Ida Bagus Gede Parama Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
The lack of utilization of natural potential and tourist facilities in Munggu Village is one of the inhibiting factors for tourism activities in Munggu Village. Through Pok Darwis, Munggu Village began to explore its natural potential to be developed, one of the natural potentials it has is a river that directly empties into Munggu Beach. Prior to the development of a research method, a research method was carried out in the site location area with the aim of seeing the physical condition of the site where the planning will be carried out, through literature studies and field observations that it is very feasible to make a new tourist facility Outfall Club. Through field observations by looking at the physical condition of the site on the riverbank, the author determines the theme of this Outfall Club using an Organic Architecture approach with several considerations that later this Outfall Club building will be designed by analogizing the shapes of the surrounding natural conditions. In this planning, a precedent study is conducted to conduct a comparative study with an existing facility with one that has not been built, the benefit of this precedent study is a reference to what functions and activities facilities will be presented in this Outfall Club plan.